You are on page 1of 10

# Prof. Dr.

## Metin Uymaz Salamc

MM403 CONTROL SYSTEMS HOMEWORK 1

Figure 1

Figure 2

Answer 1: A Main differences is closed loop and feepback lop. Figure 1 is open-loop control systems and Figure 2 is closed(feedback) control system. The number of components used in a closed-loop control system is more than that for a corresponding open-loop control system. The closed-loop control system is generally higher in cost and power. A proper combination of open loop and closed loop controls are usually less expensive and will give satisfactory overall system performance closed loop control system the reference input is modified by the actual output before entering the controller.

## Prof. Dr. Metin Uymaz Salamc Solution 2:

Figure 3 *Block Diagram Reduction Tecnique Step 1: Move summing point ahead of G1

H2/G1
U(s) + +

G1

G2

+ +

G3

G4

Y(s)

H1 H3

H2/G1.G4
U(s) + +

G1

G2

+ +

G3G4

Y(s)

## Prof. Dr. Metin Uymaz Salamc

Step 3: Combine G1 & G2 and Reduce feedback form on left, internal loop

H2/G1.G4
U(s) + +

G1G2

G3G4 1- G3G4H1
Y(s)

H3

## Step 4: Combine G1G2 & G3G4/ 1+ G3G4H1

H2/G1.G4

U(s) + +

G1G2G3G4 1- G3G4H1
Y(s)

H3

## Step 5: Reduce feedback form on left

G1G2G3G4
U(s) -

1- G3G4H1 + G2G3H2

Y(s)

H3

G1G2G3G4
U(s)

Y(s)

Y= A.G4 A=B.G3

B=C+D

C=E.G2

D=Y.H1

## A=E.G2 + Y.H1 M= G1.N

Y=G3G4 (E.G2 + Y.H.1) M-F=E F=A.H2 Y= G3G4 ( (G1.N + A.H2).G2 + Y.H1) Y= G3G4(G1 G2.N+ A.H2.G2 + Y.H1) Y= G1 G2.G3G4N + G2.G3G4 A.H2 + Y. G3G4H1 U-I=N I=Y.H3

## N=U + Y.H3 A=Y/ G4

Y= G1 G2.G3G4U- YG1 G2.G3G4 H3 - YG2.G3 H2 + YG3G4H1 Y(1+ G1 G2.G3G4 H3 + G2.G3 H2 - G3G4H1 )= U.G1 G2.G3G4

Figure 4

## Step 1: Move summing point in front of G2

G1
+
R(s) +

G2

G3
-

C(s)

H1

H2G2
Step 2: Reduce feedbacback form on right and sum G1 & G1

R(s)

G1 + G2
-

G3 1+ G3H1
C(s)

H2G2

Prof. Dr. Metin Uymaz Salamc Step 3: Reduce feedbacback form on right interloop

R(s)

G1 + G2

G3 1+ G3H1 + G2G3H2
C(s)

G3G1 + G2G3
R(s)

1+ G3H1 + G2G3H2

C(s)

## * Verify by Algebric Manuplations

C=A.G3 A=E+D-B

B=C.H1 F=R-I

D=RG1

E=F.G2

I=H2.C

E=(R-H2.C).G2

A=(R-H2.C).G2 + RG1 - C.H1 C=((R-H2.C).G2 + RG1 - C.H1)G3 C=RG2G3 - H2G2G3.C + RG1G3 - C.H1G3 C + H2G2G3.C + C.H1G3 = RG2G3 + RG1G3

i)

ii)

## C=G2V=G2(U+D)=G2[G1(R-B)+D) =G1G2(R-HC) + G2D =G1G2R G1G2HC + G2D [1 + G1G2H ] = G1G2R + G2D

iii)

V=U+D U=G1E E=R-B HC=B >> H.V.G2=B E=R-HVG2 V=G1R G1G2HV + D [1+ G1G2H] V= G1R + D

iv)

v)

Solution 4:

## Prof. Dr. Metin Uymaz Salamc

Solution 5:
a) The equation of motion for the system shown in (a)

is given by

is given by;